Phosphorus reduction by sifting fish waste meal - Lima, Ronaldo Lima De; Enke, Dariane Beatriz Schoffen; Braun, Neiva; Fracalossi, Débora Machado (Universidade Federal de Santa Maria, 2014)
Fish meal is widely included in animal feed because it contains ideal essential amino acids profile, it is rich in energy, essential fatty acids, vitamins and minerals and with >80% apparent protein digestibility in peneid shrimp. In human nutrition, studies are investigating the inclusion of fish meal in snacks, cakes, breads and cookies, as an enrichment in calcium, phosphorus, iron, protein and, especially, omega-3 fatty acids. Omega-3 fatty acids reduces heart diseases and have antithrombotic and anti-inflammatory properties (eicosapentaenoic acid), and are essential to the formation of brain tissue and retina in infants and are important during pregnancy and lactation (docosahexaenoic acid). Fish meal produced from fish waste is rich in minerals (phosphorus), which may cause eutrophication and impair water quality in aquaculture. The aim of this study was to reduce phosphorus content from commercial fish meal produced from waste by sifting (0.60 - 1.00 - 1.18 - 1.40 - 2.36 and 3.35mm mesh sizes). Fish meal samples were collected monthly for 24 months. Proximate composition of subsamples per mesh size was compared to the unsieved sample. Results indicate that sifting through a 0.60mm sieve total phosphorus and ash contents were reduced up to 32% and 36%, respectively, further to increase protein content up to 20%. Average composition of the subsamples was 47.04% ash, 5.56% of total phosphorus and 39.45% protein, suggesting that the residue of the fractionation may be marketed as a mineral and protein supplement.

A farinha de peixe é um ingrediente muito utilizado na alimentação animal, apresenta um perfil ideal de aminoácidos essenciais, é rico em energia, ácidos graxos essenciais, vitaminas e minerais, com uma digestibilidade proteica acima de 80% para os camarões peneídeos. Na alimentação humana, está sendo estudada a utilização da farinha de pescado em salgadinhos, bolos, pães e bolachas. A adição enriquece a farinha com cálcio, fósforo, ferro, proteínas, e especialmente com ácidos graxos da série ômega 3. O eicosapentaenoico atua reduzindo riscos de doenças cardíacas e possuem ações antitrombóticas e anti-inflamatórias. O ácido docosahexaenoico e o araquidônico são fundamentais na formação de tecidos nervosos e na visão das crianças, além de serem necessários para gestantes. A farinha de resíduos de filetagem de peixes caracteriza-se por um alto conteúdo de matéria mineral, o que pode promover a eutrofização e comprometer a qualidade da água na aquicultura. O objetivo deste estudo foi avaliar a redução do conteúdo de fósforo nas farinhas de resíduo de peixe produzidas comercialmente por meio de peneiragem em diferentes malhas (0,60 - 1,00 -1,18 - 1,40 - 2,36 e 3,35mm). Foram realizadas coletas mensais de uma indústria de farinha de pescado por um período de 24 meses. As amostras foram fracionadas nas peneiras e a composição proximal das frações resultantes foi comparada com a farinha integral. A maior redução de fósforo total (32%) e cinzas (36%), além da maior elevação proteica (20%) ocorreram no fracionamento com a menor malha (0,60mm). A composição média do resíduo proveniente das peneiras foi de 47,04% de cinzas, 5,56% de fósforo total e 39,45% de proteína, indicando que o resíduo do fracionamento também pode ser comercializado como suplemento mineral e proteico.
Redução do fósforo pela peneiragem da farinha de resíduos de peixes
Keywords: phosphorus; fish waste meal; fractionation; sieves.; fósforo; farinha de resíduos de peixes; fracionamento; peneiras.